Tetrabutylammonium-salt, a novel ionic medium for the synthesis of quinoline–hybrid chalcones, and its biological evaluation. (2nd January 2023) - Teja, Chitrala; Roshini, Hanumanthu; Thiyagamurthy, Pandurangan; Daniel, J. Arul; Devi, S. Asha; Vidya, R.; Nawaz Khan, Fazlur Rahman
Abstract: A series of quinoline-chalcones were synthesized from one-pot Friedlander annulation followed by Claisen–Schmidt condensation in the presence of tetrabutylammonium-ionic liquids (TBA-ILs) as a catalyst and base medium under MW-Irradiation. TBA-ILs is an emerging reaction medium instead of conventional organic solvents (VOCs). It is an efficient approach toward the C–C bond formation. The synthesized chalcones were evaluated further in vitro antimicrobial, antioxidant properties, in silico molecular docking analysis, and in vitro anticancer inhibition was achieved against MCF-7 breast cancer cell lines. Structure–activity relationships (SAR) studies were employed to improve in vitro / in vivo pharmacological activities to restrict the peripheral circulation's absorption, distribution, and metabolism. Graphical Abstract: UF0001